Pengaruh Self Efficacy Dan Dukungan Sosial Terhadap Optimisme Karyawan Kontrak Uin Syarif Hidayatullah Jakarta - Hara, Sundus; Baidun, Akhmad (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This study was conducted to determine the factors that affect optimism on employee contract, that involved 217 contract employees of UIN Syarif Hidayatullah Jakarta. Nonprobability sampling was used as sampling technique. Instruments in this study using an adaptation of optimism scale which is Life Orientation test- revised , and a modified scale of Generl Self Efficacy Scale, and the last one is adaptation of social support scale from Weiss (at Cutrona, 1987). While the method of analysis using multiple regression by SPSS software, Lisrel was used for construct validity testing. The result showed that there was a significant effect of self efficacy variables (innitiative, effort, and persistence) and social support (attachment, social integration, reassurance of worth, reliable alliance, guidance, and opportunity for nurturance) to optimism on contract employees. Although it was found that the results showed from nine independent variables there is only six independent variable that significantly affects the optimism of the contract employees was innitiative, effort, persistence, attachment, social integration and reliable alliance.Â DOI:10.15408/tazkiya.v22i2.8407